‘How are we going to harm the next trauma patient?’ Trauma care providers’ perspective on potential harm to trauma patients - Galinos Barmparas; Todd W Costantini; Avery B Nathens; Aaron R Jensen; Babak Sarani; Bryce RH Robinson (Trauma Surgery & Acute Care Open)
Background The question, “How will the next patient be harmed?” is a component of strategies used to identify latent safety risks in healthcare. We sought to survey a broad audience attending the 2023 annual conference of the American College of Surgeons–Trauma Quality Improvement Program to record their perception of the risks that might lead to patient harm at their own trauma centers.Methods Attendees were surveyed with a single free-text question “How are we going to harm the next patient?” using a quick response code. All responses were categorized into clustered themes. To report the results using a standardized reporting taxonomy, the responses were also classified according to the Joint Commission (JC) patient safety event taxonomy for near misses and adverse events. Results were reported as counts and as proportions of responders.Results During the 3-day duration of the conference, 64 participants provided 80 responses. Provider-related risk (n=16, 25.0%) was the most commonly reported category, followed closely by practice management guideline related (n=14, 21.9%) and communication gaps or failures (n=12, 18.8%). “Clinical performance” was the most commonly reported subclassification in the main category “type” of the JC patient safety event taxonomy (n=34, 53.1%), followed by patient management (n=30, 46.9%). “Human error” was the most common subclassification in the main category “cause” (n=48, 75.0%).Conclusions Human failures, rather than systems issues, were perceived to be responsible for the majority of potential harm in trauma patients by a broad audience of trauma care providers. These results require amplified focus on strategies that decrease the impact of the human element while enhancing process standardization and addressing barriers to the implementation of processes and guidelines. It might also suggest an opportunity to bring forward alternative conceptual frameworks to advance safety in trauma care.